Comparison of vaginal and oral misoprostol, for the induction of labour in women with intra-uterine foetal death - K., Kala; Rani, Anupama V.; N., Dharmavijaya M.; M., Umashankar K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Misoprostol is a prostaglandin E1 analogue, a methyl-ester of prostaglandin E1 additionally methylated at C-16. Misoprostol is an effective myometrial stimulant of pregnant uterus, selectively binding to prostanoid receptors. The objective of the study was to compare the efficacy of vaginal and oral misoprostol for the induction of labour in women with intra-uterine foetal death (IUFD). Methods: A prospective randomised clinical trial, comparing 50µg oral and 50µg vaginal misoprostol, six hourlies for a maximum of four doses for the induction of labour in women with IUFD. All patients with IUFD after 28 weeks without previous uterine surgeries, without contraindications for prostaglandins are included in the study. The study was conducted in the Department of Obstetrics and Gynecology MVJ Medical College and Research Hospital, Hoskote. Bangalore from June 2012 to June 2015. It is a tertiary institution serving predominantly rural population. The primary outcome measure was the induction to delivery time, secondary all complications were noted. Results: Twenty-five women were randomised to the vaginal route and twenty-five to the oral route. The induction to delivery time was longer with vaginal misoprostol 10.5±4.03 compared to oral misoprostol (9.58±4.9). There was no significant difference in the amount of misoprostol needed to achieve successful induction in the two groups. 3 patients needed oxytocin augmentation to complete the induction of labour. There were no cases of failed induction. The systemic side effects (shivering, diarrhoea, vomiting and pyrexia) were more common with oral misoprostol (44.5%) compared to vaginal misoprostol (20%). Conclusions: Oral misoprostol achieved successful induction of labour in women with IUFD in a shorter time than vaginal misoprostol. Both routes are equally effective in termination of pregnancy. Sublingual route is easy to administer, patient compliant, no need for internal examination, less chance of labour dysfunction, less chance of post-partum sepsis.